PERAN PEMERINTAH DALAM MENJAGA KETERSEDIAAN BERAS DI PASARAN DI ACEH, INDONESIA: KAJIAN TEORI TAS'IR AL-JABARI - Fadhlur Rahmat Muhammad (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Availability of rice at a certain time can experience shortages due to various problems. Perum Bulog has the authority to address this by intervening. One of the interventions is in the availability of rice at the market. The way to stabilize the level of rice availability and price is by providing the intended rice and adjusting it to market demand, therefore the government has the right to determine the price according to the concept of tas'ir al-jabari. The concept of tas'ir al-jabari can be carried out by Bulog in handling rice shortages. The research used in this study is qualitative descriptive. Qualitative research is a method of research that aims to understand phenomena about what is experienced by the research subject, Bulog is a state-owned company that operates in the food logistics sector. This company has various businesses including logistics and storage, surveys and pest control, plastic bag provision, transportation, food commodity trading, and retail sales. As a company with a public duty from the government, Bulog continues to carry out activities such as maintaining the basic purchase price of paddy, stabilizing prices, especially the cost price, and distributing rice to the poor and managing food stocks. Bulog's intervention in the food sector, particularly rice, involves routine agency involvement in handling various problems that arise, including rice shortages. Bulog's intervention against rice shortages can only be carried out after receiving direct orders from Bulog's central office and the Ministry of Trade. One of the interventions carried out is by cooperating with the Agriculture Office, the Central Bureau of Statistics, and the Industrial and Trade Office to conduct market operations aimed at stabilizing the market condition and preventing rice shortages from occurring.